2003
DOI: 10.1002/cncr.11310
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival in women with BRCA‐associated ovarian carcinoma

Abstract: BACKGROUND The objective of this study was to determine the clinical characteristics, treatment response, and frequency of p53 overexpression in Ashkenazi Jewish women with hereditary ovarian carcinoma. METHODS Seventy‐one Jewish women with epithelial ovarian carcinoma (EOC) were tested for the three BRCA founder mutations using single‐strand conformation polymorphism analysis, heteroduplex analysis, and protein truncation testing. Clinical and histopathologic data were reviewed retrospectively. In vitro chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
292
4
13

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(329 citation statements)
references
References 48 publications
20
292
4
13
Order By: Relevance
“…For example, patients with non-functional (mutated) BRCA1 or BRCA2, associated with hereditary breast and ovarian cancer, respond better to platinum chemotherapy owing to an increased sensitivity to DNA damage-induced cell death (Cass et al, 2003). Reintroduction of BRCA1 into cells lacking functional BRCA1 enhances resistance to both radiation and paclitaxel (Zhou et al, 2003), and cells with higher than normal levels of BRCA1 protein are resistant to killing with platinum drugs (Husain et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients with non-functional (mutated) BRCA1 or BRCA2, associated with hereditary breast and ovarian cancer, respond better to platinum chemotherapy owing to an increased sensitivity to DNA damage-induced cell death (Cass et al, 2003). Reintroduction of BRCA1 into cells lacking functional BRCA1 enhances resistance to both radiation and paclitaxel (Zhou et al, 2003), and cells with higher than normal levels of BRCA1 protein are resistant to killing with platinum drugs (Husain et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of tumour suppressors involved in ovarian cancer, much attention has focused on the role of BRCA and p53. Whereas p53 mutation appears to be frequent (Marks et al, 1991;Okamoto et al, 1991), BRCA mutation occurs in less than 10% in all diagnosed cases (Ford et al, 1994;Cass et al, 2003) and represents a small minority of ovarian cancers. Here, we identified ST-5/HTS1 as a tumour suppressor gene downregulated in the majority of ovarian primary cultures derived from malignant tumours.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to clinical and demographic factors, molecular biomarkers could be promising prognostic or predictive factors for EOC. For example, molecular epidemiological studies have demonstrated that the altered expression levels of BRCA1 and BRCA2 as a result of mutations are associated with individual variation of clinical outcomes of EOC patients 4, 5. The genomewide association study (GWAS) approach has also been used to identify susceptibility loci associated with clinical outcomes in European EOC patients 6.…”
Section: Introductionmentioning
confidence: 99%